Studying Microstructure and Crystallinity of Polypropylene in an Injection Moulded Medical Bin Lid. (2014) - Mehmood, Shahid; Arnold, Cris; Bould, David; Lavery, Nick; Alston, Sue; Sienz, Johann; Pittman, John; Cameron, Ian; Davies, John
No abstract available